Constraints and Strategies for Promotion of Dairy Enterprises - Kumari, Anuradha Ranjan; ., Laxmikant; Kundu, Pramod Kumar (Journal of Agricultural Extension Management, 2018)
This study was conducted in Deoria district in Uttar Pradesh. Out of sixteen blocks, four blocks namely Salempur, Bhatpar Rani, Bhatni and Bankata were selected for the study. Two villages from each block making a sample of eight villages and fifteen dairy entrepreneurs from each village were selected by random sampling technique. Thus 120 rural dairy entrepreneurs were selected as respondents. Constraints faced by dairy entrepreneurs in setting up dairy enterprises were grouped into four categories viz. socio-personal, economic, technological and communicational constraints. Low level of consumer awareness and motivation, poor access to finance, irregular and ineffective training programmes for upgrading know-how and skills and inadequate access to training programmes were the major constraints for dairy entrepreneurship development. The strategies suggested to strengthen the adoption of dairy enterprise by entrepreneurs included creation of proper consumer awareness for enhancing motivation, provision of institutional finance on reasonable interest and improving access and effectiveness of training programmes in dairy enterprise.